Taxonomic study of the genus Hypatopa Walsingham, 1907 (Lepidoptera: Blastobasidae) in China, with descriptions of five new species - Teng, Kaijian; Wang, Shuxia (Zootaxa, 2019)
The eight species of the genus Hypatopa Walsingham, 1907 recorded from China are reviewed, five of which are described as new: H. biprojecta, sp. nov.; H. weibaoshana, sp. nov.; H. apicirecta, sp. nov.; H. huayingshana, sp. nov.; and H. orthocera, sp. nov. Hypatopa moriutiella Sinev, 1986 and H. binotella (Thunberg, 1794) are recorded for the first time from China. Photographs of adults and genitalia are provided. A key to the Chinese species and a map showing the distribution of these species are included.